A record-high trapped field of 1.61 T in MgB2 bulk comprised of copper plates and soft iron yoke cylinder using pulsed-field magnetization. (18th June 2020) - Hirano, Tatsuya; Takahashi, Yuhei; Namba, Sora; Naito, Tomoyuki; Fujishiro, Hiroyuki
Abstract: A trapped field of B T = 1.61 T was experimentally achieved at the central surface of an MgB2 bulk composite (60 mm in diameter and 20 mm in height) at 20 K by double pulsed-field magnetization (PFM) using a split-type coil. The composite bulks consisted of two MgB2 ring bulks sandwiched by thin copper ring plates, which were then stacked, and a soft iron yoke cylinder was inserted in the central bore of the rings. The copper ring plates delayed the rise time and duration of the magnetic pulse due to eddy currents. The inserted soft iron yoke attracted the magnetic flux and enhanced the trapped field strength mainly due to its large permeability. As a result, the trapped field was enhanced from B T = 0.34 T for the single MgB2 ring bulk without the copper plates and soft iron yoke to B T = 1.00 T for the composite with both copper plates and the soft iron yoke. The inserted soft iron yoke can be exploited to enhance the trapped field because the intrinsic B T of the single MgB2 ring bulk was smaller than the saturation field of the yoke (∼2 T). Using an optimized second pulse application after suitable flux trapping from the first pulse application, the trapped field was enhanced considerably to B T (2nd) = 1.61 T, which is a record-high trapped field for an MgB2 bulk by PFM to date. The combination of the longer magnetic pulse application by the copper plates, the enhancement of the effective applied field by the inserted soft iron yoke, and the double pulse application using split-type coil is an effective technique to enhance the trapped field in the MgB2 bulk using PFM.